2021
DOI: 10.1155/2021/5195508
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Vision Sensor‐Based Real‐Time Fire Detection in Resource‐Constrained IoT Environments

Abstract: Fire detection and management is very important to prevent social, ecological, and economic damages. However, achieving real-time fire detection with higher accuracy in an IoT environment is a challenging task due to limited storage, transmission, and computation resources. To overcome these challenges, early fire detection and automatic response are very significant. Therefore, we develop a novel framework based on a lightweight convolutional neural network (CNN), requiring less training time, and it is appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Yar at el. [17] developed a novel lightweight convolutional neural network (CNN) framework that requires a short training time and can be applied to devices with limited resources. Frizzi et al [18] proposed a specialized CNN-based design for ames and smoke identi cation.…”
Section: Traditional and Deep Learning Methodsmentioning
confidence: 99%
“…Yar at el. [17] developed a novel lightweight convolutional neural network (CNN) framework that requires a short training time and can be applied to devices with limited resources. Frizzi et al [18] proposed a specialized CNN-based design for ames and smoke identi cation.…”
Section: Traditional and Deep Learning Methodsmentioning
confidence: 99%
“…In this work, we developed an effective and efficient model for face mask detection based on the Convolutional Neural Network (CNN). Motivated by the high performance of CNN in several domains such as video analysis [ 28 ], classification [ 29 ], time-series data analysis [ 30 ], electricity prediction [ 31 ], and many others, in this work, we developed a CNN-based model for face mask detection. The visual representation of the proposed work is given in Figure 1 , which includes two main phases of data augmentation and the proposed model.…”
Section: Proposed Modelmentioning
confidence: 99%
“…Arshad et al [3] suggested a new intrusion prevention scheme for IoT systems with limited resources. As a result, intrusion protection is disabled for IoT devices and the edge router.…”
Section: Related Workmentioning
confidence: 99%
“…To protect and guard against attacks from infected IoT devices, intelligent intrusion detection techniques for IoT devices must be designed and built. However, many intrusion detection devices require a significant amount of computing power and energy [3].…”
Section: Introductionmentioning
confidence: 99%